Odpowiedź:
zad.11
a) =[tex]\sqrt{6^{2}*6 }[/tex]=6[tex]\sqrt{6}[/tex]
b)=[tex]\sqrt{7^{2}*7^{2}*7 }[/tex]=7*7[tex]\sqrt{7}[/tex]=49[tex]\sqrt{7}[/tex]
c)=[tex]\sqrt{3^{2}*3^{2} *3^{2}*3^{2}*3 }[/tex]=3*3*3*3[tex]\sqrt{3}[/tex]=81[tex]\sqrt{3}[/tex]
d) =[tex]\sqrt{5^{6}*5 }[/tex]=[tex]5^{3}[/tex][tex]\sqrt{5}[/tex]=125[tex]\sqrt{5}[/tex]
e) =[tex]\sqrt[3]{5^{3} *5}[/tex]=5[tex]\sqrt[3]{5}[/tex]
f) =[tex]\sqrt[3]{4^{3}*4^{2} }[/tex]=4[tex]\sqrt[3]{4^{2} }[/tex]=4[tex]\sqrt[3]{16}[/tex]
zad.
a) =2[tex]\sqrt{2^{2}*2 }[/tex]-3[tex]\sqrt{2}[/tex]=2*2[tex]\sqrt{2}[/tex]-3[tex]\sqrt{2}[/tex]=4[tex]\sqrt{2}[/tex]-3[tex]\sqrt{2}[/tex]=[tex]\sqrt{2}[/tex]
c)= [tex]\sqrt[3]{5^{3}*5^{2} }[/tex]-[tex]\sqrt[3]{-5^{2} }[/tex]=5[tex]\sqrt[3]{5^{2} }[/tex]-(-[tex]\sqrt[3]{5^{2} }[/tex])=5[tex]\sqrt[3]{5^{2} }[/tex]+[tex]\sqrt[3]{5^{2} }[/tex]=6[tex]\sqrt[3]{25}[/tex]
Szczegółowe wyjaśnienie: